2011
DOI: 10.1523/jneurosci.1781-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Dopamine Receptor-Mediated Opiate Reward Memory Switch in the Basolateral Amygdala–Nucleus Accumbens Circuit

Abstract: The basolateral amygdala (BLA), ventral tegmental area (VTA), and nucleus accumbens (NAc) play central roles in the processing of opiate-related associative reward learning and memory. The BLA receives innervation from dopaminergic fibers originating in the VTA, and both dopamine (DA) D1 and D2 receptors are expressed in this region. Using a combination of in vivo single-unit extracellular recording in the NAc combined with behavioral pharmacology studies, we have identified a double dissociation in the functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 31 publications
4
81
0
Order By: Relevance
“…1a). The BLA-shell projection has also been implicated in morphine reward (Lintas et al 2011). In this study, dopamine receptor antagonists in the BLAwere capable of altering neurophysiological responses of shell neurons to morphine (Lintas et al 2011).…”
Section: Amygdala Outputsmentioning
confidence: 67%
See 1 more Smart Citation
“…1a). The BLA-shell projection has also been implicated in morphine reward (Lintas et al 2011). In this study, dopamine receptor antagonists in the BLAwere capable of altering neurophysiological responses of shell neurons to morphine (Lintas et al 2011).…”
Section: Amygdala Outputsmentioning
confidence: 67%
“…The BLA-shell projection has also been implicated in morphine reward (Lintas et al 2011). In this study, dopamine receptor antagonists in the BLAwere capable of altering neurophysiological responses of shell neurons to morphine (Lintas et al 2011). The BLA potentiates shell neuronal activity in part via stimulation of NMDA-Rs (Floresco et al 1998;Floresco et al 2001).…”
Section: Amygdala Outputsmentioning
confidence: 69%
“…Furthermore, animal studies have shown that D1R antagonism blocks nicotine motivation in nondependent mice (36). A recent study showed that blockade of D1R but not D2R transmission prevented acquisition of opiate-reward memory in nondependent rats, and D2R but not D1R blockade prevented opiate-reward encoding in dependent and withdrawn rats (37). However, previous studies suggest that both acute nicotine and opiate reward are mediated by the non-DAergic brainstem tegmental pedunculopontine (TPP) nucleus (9,12,21), and thus must involve separate cells in the TPP that are thought to mediate burst-firing of VTA DA neurons (5, 14); burst-firing that we show here is involved in the response to acute nicotine.…”
Section: Discussionmentioning
confidence: 99%
“…113,114 In particular, the pyramidal neurons of the basolateral amygdala receive input from the VTA. In saline-treated amygdala slices, DA reduced the amplitude of excitatory postsynaptic currents (EPSCs) by inhibiting α-amino-3-hydroxy-5-mehtyl-4-isoxazoleproprionic acid (AMPA) receptors.…”
Section: Molecular Changes In the Amygdalamentioning
confidence: 99%